Financial hardship associated with colorectal cancer survivorship: The role of asset depletion and debt accumulation. Issue 9 (21st June 2018) - Hanly, Paul; Maguire, Rebecca; Ceilleachair, Alan O; Sharp, Linda
Abstract: Objective: To estimate the prevalence of financial objective stress and subjective strain among colorectal cancer survivors and assess associated financial coping factors in Ireland, which has a mixed public‐private health care system. Methods: Colorectal cancer survivors were identified from the National Cancer Registry, and a sample of 496 respondents were included in the analysis. A postal survey collected information on survivor demographics, socio‐economic background, medical characteristics, cancer‐related financial hardship, debt accumulation, and asset depletion. Cancer‐related financial objective stress and subjective strain were used as dependent variables in logistic regression analysis. Results: Approximately 2 in 5 survivors experienced objective stress (40.9%) or subjective strain (39.4%). Depletion of savings (49.1%) was the most prevalent form of financial coping strategy. Factors significantly associated with increased objective stress were having a stoma (OR = 2.1; 95% CI, 1.1‐3.9), using savings (OR = 9.4; 95% CI, 4.9‐18.0), formally borrowing money (OR = 3.1; 95% CI, 1.0‐9.6), and loans from family members/friends (OR = 3.8; 95% CI, 1.9‐7.8). Not working (excluding retirees) (OR = 0.44; 95% CI, 0.20‐0.96) was associated with decreased objective stress. Significant predictors of subjective strain included having dependents, a stoma, using savings (OR = 5.3; 95% CI, 2.9‐9.5), and loans from family members/friends (OR = 2.0; 95% CI, 1.1‐3.9) but excluded borrowing money. Conclusions: Cancer‐related financial objective stress and subjective strain are common in colorectal cancer survivors, even where all citizens are entitled to publicly funded care, but the financial coping strategies significantly associated with these 2 measures differed. These findings will help inform targeted measures across disparate health care systems and survivor groups to alleviate financial hardship.